Remarkable size-spectra stability in a marine system undergoing massive invasion. (31st July 2017) - Buba, Yehezkel; van Rijn, Itai; Blowes, Shane A.; Sonin, Oren; Edelist, Dor; DeLong, John P.; Belmaker, Jonathan
Abstract : The Mediterranean Sea is an invasion hotspot, with non-indigenous species suspected to be a major driver behind community changes. We used size spectra, a reliable index of food web structure, to examine how the influx of Red Sea fishes into the Mediterranean Sea has impacted the indigenous species community. This is the first attempt to use changes in the size spectra to reveal the effect of biological invasions. We used data from trawl catches along Israel's shoreline spanning 20 years to estimate changes in the community size spectra of both indigenous and non-indigenous species. We found that the relative biomass of non-indigenous species increased over the 20 years, especially for small and large species, leading to a convergence with the indigenous species size spectra. Hence, the biomass of indigenous and non-indigenous species has become identical for all size classes, suggesting similar energetic constraints and sensitivities to fishing. However, over this time period the size spectrum of indigenous species has remained remarkably constant. This suggests that the wide-scale invasion of non-indigenous species into the Mediterranean may have had little impact on the community structure of indigenous species.